Critical Determinant of Stroke Risk to Timorese People: Retrospective Analysis - Carvalho, Marcos; S.M. Exposto, Levi Anatolia; da Conceição Pacheco, Aniceto (Rifa'Institute, 2024)
Stroke is the leading cause of disability and the second most ruthless cause of death globally, in particular Timor-Leste. This paper aims to identify the risk factors for stroke in Timor-Leste. This study conducted a systematic literature review on three major databases PUBMED, BMJ, and Google Scholar. 50 articles were selected based on the inclusion and exclusion criteria. Only 4 articles produced data related to stroke in Timor-Leste. Data was analyzed using the PRISMA method. We found that the risk factors for stroke in Timor-Leste are high blood pressure, smoking, high cholesterol, Alcohol consumption, and physical inactivity. We conclude that Timor-Leste people need to manage and control their lifestyle to control hypertension, smoking, maintaining a healthy diet, exercising regularly, limiting alcohol consumption, managing cholesterol, maintaining a healthy weight, and getting regular medical check-ups can help monitor risk factors for stroke. The implication of this study is healthy population is crucial for the supply of human resources to economic sectors.